Urban density and parametric urbanism: computational code for simulating urban indices - Cavalcanti, Isabella (2020)
The lack of knowledge and the little application of computational tools to visualize urban indexes make it difficult for planners and managers to understand the possible impacts of these indexes on the form and occupation of urban land and, consequently, produce cities that do not meet the sustainability principles of urbanity. In view of the plurality of meanings and applications, the use of urban density as an index must be very well explained in the regulations and the result of concrete studies. This article is the result of a research centered on the construction of a computational code aimed at simulating urban indexes that deal with urban density, through the development of an algorithm in the parametric software Rhinoceros3D and in the Grasshopper plug-in. The general objective is to develop a computational system to carry out experiments and predictions of parameters that order the occupation of urban land. From the scenarios resulting from the simulation and the automation of data related to urban density, it was possible to perceive that the insertion of computational technologies can significantly contribute to the search process for better urban projects and management.